2022
DOI: 10.4103/ijo.ijo_2030_21
|View full text |Cite
|
Sign up to set email alerts
|

Neurotization of the human cornea – A comprehensive review and an interim report

Abstract: We present a comprehensive review of existing literature on surgical corneal neurotization (SCN) as a treatment modality for neurotrophic keratopathy (NK) with an interim report of seven cases where SCN was performed using the indirect approach and followed up till 18 months postoperatively to look for improvement in ocular surface, corneal sensations, and nerve regeneration by using in vivo confocal microscopy (IVCM). A literature search was performed for publications with keywords “cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…A similar observation of corneal sensation improvement at a 3-month follow-up with maximal sensation at 6 months was reported by Kim et al [ 23 ] in herpetic NK. However, previous studies [ 5 , 19 , 22 ] and the recently published Rathi et al [ 24 ] interim reports observed objective improvement in corneal sensation at 5–6 months. The return of corneal sensation observed was significant in our study, although the absolute value to the contralateral normal cornea was not attained ( Fig 5 ), which is consistent with the results of previous studies [ 5 , 19 ].…”
Section: Discussionmentioning
confidence: 96%
“…A similar observation of corneal sensation improvement at a 3-month follow-up with maximal sensation at 6 months was reported by Kim et al [ 23 ] in herpetic NK. However, previous studies [ 5 , 19 , 22 ] and the recently published Rathi et al [ 24 ] interim reports observed objective improvement in corneal sensation at 5–6 months. The return of corneal sensation observed was significant in our study, although the absolute value to the contralateral normal cornea was not attained ( Fig 5 ), which is consistent with the results of previous studies [ 5 , 19 ].…”
Section: Discussionmentioning
confidence: 96%
“…We documented the full ophthalmic history and demographic profile (sex, age, and nationality) of each patient. All patients underwent a detailed ocular examination including a comprehensive anterior segment slit-lamp examination (Haag-Streit Photo-Slit Lamp BX 900; Haag-Streit, Koeniz, Switzerland); posterior segment assessment under slit-lamp using a + 90 D auxiliary lens (Volk Optical Inc., Mentor, OH, USA) if media did not preclude an adequate view of the posterior segment; measurement of best-corrected distance visual acuity (BCDVA) and uncorrected distance visual acuity (UCDVA) using a Snellen chart (Auto Chart Projector CP 670; Nidek Co., Ltd., Gamagori, Japan); intraocular pressure measurement (Applanation Tonometer 900; Haag-Streit); corneal sensation assessment [ 16 ] in the four corneal quadrants using the cotton wisp test [ 17 ] ; and in certain cases, corneal scraping for culture and antimicrobial sensitivity testing [ 18 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Acquired NK may be caused by herpes simplex or zoster infections, tumors, intraoperative injury, and trauma such as thermal and chemical burns 11,12 . More rarely, acquired causes of NK can be due to systemic neuropathies, such as diabetes mellitus or leprosy, or metabolic etiologies such as vitamin B12 deficiency [13][14][15][16] . Iatrogenic causes range from contact lens misuse to the chronic use of some topical medications, such as those used to treat glaucoma, in addition to damage during ocular or CND surgery 17 .…”
Section: Pathogenesis Of Corneal Anesthesia In Adults and Childrenmentioning
confidence: 99%